2013
DOI: 10.1016/j.ijpsycho.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Ultradian and circadian modulation of dream recall: EEG correlates and age effects

Abstract: a b s t r a c t a r t i c l e i n f oDreaming occurs during non-rapid eye movement (NREM) and rapid eye movement (REM) sleep, which both are regulated by homeostatic, ultradian, and circadian processes. However, the magnitude of how ultradian REM and NREM sleep and its EEG correlates impact onto dream recall remains fairly unknown. In this review, we address three questions: 1. Is there an ultradian NREM-REM sleep modulation in successful dream recall, which is gated by the circadian clock? 2. What are the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
(86 reference statements)
1
10
0
Order By: Relevance
“…Many studies did attempt to link dream recall or dream content attributes with specific neurophysiological indicators, most commonly with electroencephalograpy (EEG) measures, but such studies provide mixed results at best. For example, EEG correlates of remembering dreaming after REM sleep awakenings vary widely, from power reductions in alpha (Bertolo et al, 2003;Esposito et al, 2004;Chellappa and Cajochen, 2013), delta (Esposito et al, 2004), frontal beta (Chellappa et al, 2011), and 4-to 14-Hz activity (Lehmann et al, 1981), to power increases in 40-Hz (Llinas and Ribary, 1993), occipital beta (Chellappa et al, 2011), and theta (Marzano et al, 2011;Scarpelli et al, 2015). Studies attempting to uncover EEG signatures for specific dream qualities were quite uncommon (e.g.…”
Section: Limits Of Traditional Rem Sleep Dream Studiesmentioning
confidence: 99%
“…Many studies did attempt to link dream recall or dream content attributes with specific neurophysiological indicators, most commonly with electroencephalograpy (EEG) measures, but such studies provide mixed results at best. For example, EEG correlates of remembering dreaming after REM sleep awakenings vary widely, from power reductions in alpha (Bertolo et al, 2003;Esposito et al, 2004;Chellappa and Cajochen, 2013), delta (Esposito et al, 2004), frontal beta (Chellappa et al, 2011), and 4-to 14-Hz activity (Lehmann et al, 1981), to power increases in 40-Hz (Llinas and Ribary, 1993), occipital beta (Chellappa et al, 2011), and theta (Marzano et al, 2011;Scarpelli et al, 2015). Studies attempting to uncover EEG signatures for specific dream qualities were quite uncommon (e.g.…”
Section: Limits Of Traditional Rem Sleep Dream Studiesmentioning
confidence: 99%
“…Many studies did attempt to link dream recall or dream content attributes with specific neurophysiological indicators, most commonly with electroencephalograpy (EEG) measures, but such studies provide mixed results at best. For example, EEG correlates of remembering dreaming after REM sleep awakenings vary widely, from power reductions in alpha ( Bertolo et al , 2003 ; Esposito et al , 2004 ; Chellappa and Cajochen, 2013 ), delta ( Esposito et al , 2004 ), frontal beta ( Chellappa et al , 2011 ), and 4- to 14-Hz activity ( Lehmann et al , 1981 ), to power increases in 40-Hz ( Llinas and Ribary, 1993 ), occipital beta ( Chellappa et al , 2011 ), and theta ( Marzano et al , 2011 ; Scarpelli et al , 2015 ). Studies attempting to uncover EEG signatures for specific dream qualities were quite uncommon (e.g.…”
Section: Limits Of Traditional Rem Sleep Dream Studiesmentioning
confidence: 99%
“…For instance, after awakenings from NREM sleep, two studies found that a successful dream recall was associated with a decreased alpha power (8–12 Hz) in the sleep EEG preceding awakening (Esposito et al, 2004; Marzano et al, 2011), while another study found that successful dream recall was associated with increased alpha power (Takeuchi et al, 2003). The variability of these results (for a review see Chellappa and Cajochen, 2013) may be due to the difficulty in knowing for sure whether or not the reported dream occurred in the few minutes preceding awakening. Studies using such an approach may thus have been biased by dream reports resulting from dreams produced outside the few minutes of sleep investigated.…”
Section: Introductionmentioning
confidence: 99%